Kontemplative aktiviteter i skolen i et livsverdensperspektiv – Observationer mellem åbenhed og refleksion. - Kolmos, Marie (Psyke & Logos, 2016)
This article deals with how contemplative activities in a public school setting and a Waldorf school setting emerge in a phenomenological inspired life-world perspective. It starts with a short introduction to ‘contemplative activities’ and how they can be understood in connection to school settings as a way for the teacher to direct the attention of the children and foster mental health and well-being. In the qualitative literature, contemplative activities in schools are often described as part of a mindfulness or yoga inspired intervention. The two schools presented in this paper both have contemplative activities as an integrated part of their everyday school life. In these settings the teachers use poetry, music and movement to direct the attention of the children either as an opening to the subject learning, between subject activities or when there is a need for a break during lessons. The purpose of this article is to describe and discuss what emerges when the researcher applies a life-world perspective to these school settings with a phenomenological focus on the bodily becoming of the children in the classroom.